Impactos da política estadual de incentivos fiscais sobre a arrecadação de ICMS No Estado do Ceará - Sousa, Paulo Francisco Barbosa (2008)
The analysis of the tax incentive´s policy practiced by the State of Ceara and its impacts from the ICMS tax collections have been the focus of this work. Through a economic analysis of the period between 1995 to 2006, tried to identify externalities caused by the adoption and intensification of the tax incentives policy in this state. The study was conducted using basically the document analysis. The data used are secondary and were collected through a literature search and studies on the Internet. The state´s ICMS tax collections in this period has shown a tendency to growth. However, the participation of segments linked to the industrial sector, sectors that receive tax incentives, are cutting themselves over this analysis period. Other sectors such as electrical energy, communication services and fuels showed a strong increase in participation of ICMS tax collection. The research results demonstrate that there is an intimate relationship between the increase the ICMS tax collection and the increase of the participation of industries related to services. This fact indicates that the policy of tax incentives practiced by the state of Ceara is being financed indirectly by the people who through an intensive income transfer caused by the increased participation of the basic services´s sectors, electricity and communication and further fuels, in the tax structure.